Effect of the steam bath on resting cardiovascular parameters in healthy volunteers. Issue 3 (September 2021) - Pandiaraja, M.; Vanitha, A.; Maheshkumar, K.; Venugopal, V.; Poonguzhali, S.; Radhika, L.; Manavalan, N.
Abstract: Background: The steam bath is a widely used hydriatic application in the management of many clinical conditions. However, there is a paucity of evidence supporting its clinical benefits. The objective of the current study is to find the immediate effects of steam bath on resting cardiovascular parameters among healthy volunteers. Methods: The current study is a randomized control trial including 80 healthy volunteers recruited from a medical college in Chennai, India. They were randomly assigned to either intervention group (n-40) or control group (n-40) by simple lottery method. Intervention group (n-40) underwent steam bath followed by shower. In contrast, the control group (n-40) took shower alone at a water temperature of 27 °C. Systolic (SBP), diastolic blood pressure (DBP) and heart rate (HR) were measured at baseline, immediately after the steam/ shower bath and during the recovery periods (10 and 30 min after the steam/ shower bath). Results: The SBP increased quickly after the steam bath (8.9 ± 2.4 mmHg), and reduced (5.0 ± 2.9 mmHg) at 10thmin and (10.7 ± 3.7 mmHg) at 30 min of the recovery period (p < 0.01). Whereas in the control group, SBP increased from baseline immediately, at 10 min and 30 min of the recovery period (4.2 ± 1.9 mmHg, 7.3 ± 3.9 mmHg and 5.3 ± 3.8 mmHg). DBP decreased significantly quickly after steam bath (9.5 ± 4.2 mmHg), at 10 min (12.7 ± 4.4 mmHg) and 30 min (11.3 ± 4.8 mmHg) of the recovery period and no such changes were observed in the control group (P > 0.05). Conclusion: The current study indicated that steam bath potentially improves cardiovascular function by reducing blood pressure in normal healthy subjects. Further studies are needed to confirm our findings in different populations and also assess the associations of steam bath with cause-specific cardiovascular events.